Nicotinamide benefited amino acid metabolism and rumen fermentation pattern to improve growth performance of growing lambs - YuAng Wang; Hao Wu; Yiwei Zhang; Mingfeng Fei; Zhefeng Li; Daxi Ren; Chong Wang; Xiaoshi Wei (Animal Bioscience)
Objective Nicotinamide (NAM) is easily degraded in the rumen, but the rumen-protected NAM (RPN) supplementation might enable the use of NAM in ruminants. This study aimed to elucidate the effects of RPN supplementation on growth performance, rumen fermentation, antioxidant status and amino acid (AA) metabolism in growing lambs. Methods A total of 128 healthy and similar lambs (21.3±0.28 kg, 70±6.3 days of age) were allotted to 1 of 4 groups. The treatments were 0, 0.5, 1, and 2 g/d RPN supplementation. The RPN products (50% bioavailability) were fed at 0700 h every day for 12 weeks. All lambs were fed the same pelleted total mixed rations to allow ad libitum consumption and had free access to water. Results The RPN tended to increase the average daily gain and feed efficiency. The tendencies of RPN×day interaction were found for dry matter intake during the entire study (p = 0.078 and 0.073, respectively). The proportions of acetic acid, isobutyric acid and isovaleric acid were decreased, whereas the proportions of propionic acid and valeric acid were increased (p<0.05). The ratio of acetic acid to propionic acid was decreased (p<0.05). Moreover, the antioxidative status was enhanced and the glucose concentration was increased by RPN (p<0.05). In addition, 17 AAs were detected in plasma, of which 11 AAs were increased by RPN (p<0.05). Plasma metabolomics analysis identified 1,395 compounds belonging to 15 classes, among which 7 peptides were significantly changed after RPN supplementation. Conclusion Overall, the results suggested that RPN supplementation favoured the rumen fermentation pattern to propionic acid-type with benefited glucose metabolism, enhanced antioxidant capacity, and changed the AA and small peptide metabolism. This study provides a new perspective for studying the relationship between vitamin and AA metabolism.